Desenvolvimento de produtos sustentáveis: o papel da gestão de pessoas - Jabbour, Charbel José Chiappetta [UNESP]; Santos, Fernando César Almada (Fundação Getulio Vargas, 2007)
This article enlightens the debate on the integration between people management and sustainable product development (SPD) an issue that lacks theoretical and practical perspectives, especially for the national scientific production. The article adopts a reflexive approach to the main contributions to SPD given by the functional and competitive dimensions of people management. As a result, it proposes a model for improving the process of developing environmentally sustainable products. It also presents the implications of that interaction for the HR area, as well as recommendations for future researches.

Este artigo lança luzes sobre o debate acerca da integração entre administração de pessoas e desenvolvimento de produtos sustentáveis (DPS) que carece de perspectivas teóricas e práticas, principalmente quanto à produção científica nacional. Para tanto, desenvolveu-se uma abordagem reflexiva sobre as principais contribuições das dimensões funcionais e competitivas da gestão de pessoas para o DPS. Como resultado, é proposto um construto para a melhoria do processo de desenvolvimento de produtos ambientalmente sustentáveis e são apresentadas as implicações dessa interação para a área de recursos humanos, além de recomendações para pesquisas vindouras.
Sustainable product development: the role of people management
Keywords: people management; environmental management; sustainable products; gestão de pessoas; gestão ambiental; produtos sustentáveis